Diferença entre templates de autômatos celulares unidimensionais binários - Soares Junior, Zorandir (2016)
Templates are formal representations for sets of one-dimensional cellular automata created by means of a generalisation of the classical state transition tables. Algorithms already do exist in the literature that generate templates for static properties of cellular automata rules, as well as others that perform operations such as intersection between templates and template expansion. Here, we introduce the exception template operation, the operation of di erence between templates, and explain the functioning of the algorithm of those operations, which have been implemented in the CATemplates package of the Mathematica software. We also discuss the possibility of using templates in the context of the parity problem {namely, the determination of the parity of 1s in a cyclic binary con guration of odd length{ with the support of the operation of di erence between templates, and of the template generation of parity conserving and state conserving cellular automata.